2019
DOI: 10.7150/ijbs.32899
|View full text |Cite
|
Sign up to set email alerts
|

A robust 6-mRNA signature for prognosis prediction of pancreatic ductal adenocarcinoma

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is one of the most fatal malignancies worldwide. PDAC prognostic and diagnostic biomarkers are still being explored. The aim of this study is to establish a robust molecular signature that can improve the ability to predict PDAC prognosis. 155 overlapping differentially expressed genes between tumor and non-tumor tissues from three Gene Expression Omnibus (GEO) datasets were explored. A least absolute shrinkage and selection operator method (LASSO) Cox regression model w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 49 publications
1
13
0
Order By: Relevance
“…Establishing gene scoring models contribute to quantify the prognostic evaluation criteria and increasing studies have performed successful precedents in this regard. [ 12 , 15 , 16 ] Our current study established a six-gene prognosis predictive model in patients with PaCa and validated the prognostic value of this model in total PaCa patients and several subgroups, confirming that the six-gene prognosis model could exactly predict the OS of patients with PaCa.…”
Section: Discussionsupporting
confidence: 65%
“…Establishing gene scoring models contribute to quantify the prognostic evaluation criteria and increasing studies have performed successful precedents in this regard. [ 12 , 15 , 16 ] Our current study established a six-gene prognosis predictive model in patients with PaCa and validated the prognostic value of this model in total PaCa patients and several subgroups, confirming that the six-gene prognosis model could exactly predict the OS of patients with PaCa.…”
Section: Discussionsupporting
confidence: 65%
“…By utilizing public databases, such as TCGA and GEO, multiple prediction models based on gene expression have been established that can reliably predict prognosis of PDAC patients following surgical resection and reflect the biological behavior of the disease [5,6]. Recently, Zhou C et al established a robust six-gene signature to predict the OS of PDAC through comprehensive mining of OS-related DEGs [7]. Rigorous validations revealed that the proposed gene signature was able to distinguish high-risk and low-risk patients with significantly different OS.…”
Section: Ivyspringmentioning
confidence: 99%
“…In recent years, progress in next-generation sequencing technologies has allowed researchers to establish several prognostic signatures for PDAC [ 17 22 ]. All of these models have robust predictive ability, but they are not accurate enough, as most of them are derived from the single TCGA-PAAD dataset.…”
Section: Introductionmentioning
confidence: 99%